Heart rate variability in the standing position reflects training adaptation in professional soccer players - Ravé, G.; Fortrat, J. O. (European Journal of Applied Physiology, 2016)
Purpose: To show that heart rate variability (HRV) in the standing position better reflects the way in which athletes adapt to training in so-called intermittent sports than the indicator of resting parasympathetic tone usually employed in endurance sports. Methods: Twenty professional soccer players (intermittent sport) took part in a 5-week training session divided into three successive periods: "Warm-up", "Intensive training" and "Tapering". At the beginning and end of each of the three periods, a stand test was carried out and the heart rate was recorded, beat by beat (Polar Team 2). We analysed HRV to determine the indicator mostly used to demonstrate training adaptation in endurance sports (lnRMSSD supine, natural logarithm of root mean square of the successive differences) as well as indicators obtained by means of spectral analysis in both supine and standing position. Results: A decrease in heart rate was observed in the supine position at rest during training (-5.2 ± 1.3 bpm) while lnRMSSD and spectral analysis indicators remained unchanged. The "Warm-up" caused an increase in spectral analysis total power in standing position which was further highlighted by "Tapering" (3.39 ± 0.09, 3.61 ± 0.08 and 3.65 ± 0.09 log ms2, respectively). However, the autonomic changes are probably more complex than a change in autonomic activity or balance since spectral analysis autonomic indicators remained unchanged. Conclusions: HRV in the standing position could monitor training adaptation in intermittent sports contrary to the indicator usually employed in endurance sports. However, the significance of the HRV change in the standing position during training remains unclear.